2006
DOI: 10.1128/aac.00127-06
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nonnucleoside Inhibitors That Select Nucleoside Inhibitor Resistance Mutations in Human Immunodeficiency Virus Type 1 Reverse Transcriptase

Abstract: Mutations in and around the catalytic site of the reverse transcriptase (RT) of human immunodeficiency virus type 1 (HIV-1) are associated with resistance to nucleoside RT inhibitors (NRTIs), whereas changes in the hydrophobic pocket of the RT are attributed to nonnucleoside RT inhibitor (NNRTI) resistance. In this study, we report a novel series of nonnucleoside inhibitors of HIV-1, exemplified by VRX-329747 and VRX-413638, which inhibit both NNRTI-and NRTI-resistant HIV-1 isolates. Enzymatic studies indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
62
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 31 publications
1
62
0
Order By: Relevance
“…Previous biochemical studies by our group have shown that INDOPY-1 binds preferentially following incorporation of pyrimidines, stabilizes the RT-DNA/DNA complex in its post-translocated state, and blocks DNA synthesis in a reversible manner (5). While the resistance profile for this inhibitor is unique, changes in susceptibility to INDOPY-1 have been associated with a number of mutations that likewise change susceptibility to NRTIs (5,6). Here we studied the biochemical phenotypes associated with these changes to provide novel insight into both mechanisms of resistance, and the binding properties of INDOPY-1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous biochemical studies by our group have shown that INDOPY-1 binds preferentially following incorporation of pyrimidines, stabilizes the RT-DNA/DNA complex in its post-translocated state, and blocks DNA synthesis in a reversible manner (5). While the resistance profile for this inhibitor is unique, changes in susceptibility to INDOPY-1 have been associated with a number of mutations that likewise change susceptibility to NRTIs (5,6). Here we studied the biochemical phenotypes associated with these changes to provide novel insight into both mechanisms of resistance, and the binding properties of INDOPY-1.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these findings suggest that the binding site for indolopyridones and nucleotide substrates can at least partially overlap. The resistance profile of INDOPY-1 provides further independent evidence for this notion (5,6). In vitro selection experiments and phenotypic susceptibility measurements with clinical isolates and constructs generated by site-directed mutagenesis suggest that most mutations associated with decreased susceptibility to INDOPY-1 are clustered around the dNTP binding site.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…The observed preference of PFA for the pre-translocational form of the polymerase⅐DNA complex was recently validated by the first crystal structure of PFA bound to a DNA polymerase, which showed PFA binding and stabilization of the closed enzyme conformation leading to the formation of an untranslocated form of the polymerase⅐DNA complex (14). In contrast, the more recently discovered scaffold of indolopyridones (INDOPY-1) (15,16) traps RT in the post-translocational state (15). Owing to its proposed binding mechanism, INDOPY-1 has been referred to as a nucleotide-competing RT inhibit (17).…”
mentioning
confidence: 99%